2019
DOI: 10.1101/535575
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Argonaute bypasses cellular obstacles without hindrance during target search

Abstract: Argonaute (Ago) proteins are key players in gene regulation in eukaryotes and host defense in prokaryotes. For specific interference, Ago relies on base pairing between small nucleic acid guides and complementary target sequences. To efficiently scan nucleic acid chains for potential targets, Ago must bypass both secondary structures in mRNA and single stranded DNA as well as protein barriers. Through single-molecule FRET, we reveal that lateral diffusion is mediated mainly through protein-nucleic acid interac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…If two targets are present on one strand, one did not only observe the addition of binding signatures with a lower FRET state, but also a shuttling signature: the transition from one binding site to the other without interruption (Figure 6(b)) [67] Since it appeared that the Ago complex did not dissociate from the strand during translocation from one target to the other target, it was suggested that lateral diffusion took place between the two targets [67]. This has also been observed for a pAgo from the mesophilic bacterium Clostridium butyricum (CbAgo) [71,72]. Kinetic modelling suggested that if lateral diffusion would place, a linear relation would exist between distance and shuttling time.…”
Section: Hidden Rapid Dynamics In Target Searchmentioning
confidence: 68%
See 4 more Smart Citations
“…If two targets are present on one strand, one did not only observe the addition of binding signatures with a lower FRET state, but also a shuttling signature: the transition from one binding site to the other without interruption (Figure 6(b)) [67] Since it appeared that the Ago complex did not dissociate from the strand during translocation from one target to the other target, it was suggested that lateral diffusion took place between the two targets [67]. This has also been observed for a pAgo from the mesophilic bacterium Clostridium butyricum (CbAgo) [71,72]. Kinetic modelling suggested that if lateral diffusion would place, a linear relation would exist between distance and shuttling time.…”
Section: Hidden Rapid Dynamics In Target Searchmentioning
confidence: 68%
“…A point worthy of note here is that the residence times for individual targets were found to be much shorter than the residence time of a single target [72]. This indicates that apparent stable binding traces contain rapid excursions away from and back to the target site.…”
Section: Hidden Rapid Dynamics In Target Searchmentioning
confidence: 80%
See 3 more Smart Citations